Internet of Things (IoT) design based on smart farming with solar panels in an agriculture laboratory - Nugraha, Made Dika; Mahabojana, Kadek Agus; Pratama, Gede Agus Surya (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
The implementation of smart farming still uses AC electricity resources which is estimated to be less effective in its implementation due to wasted electricity costs. As well as the lack of a crop monitoring system by farmers, crop yields are not optimal. This research aims to produce a smart farming system that is used for hydroponic plants to monitor plant conditions periodically and the automatic watering process and nutrient measurements are more efficient, online to the network with the IoT concept, and saves energy by utilizing solar panels. This research is quantitative research with experimental methods. The stages in this system include flowcharts and block diagrams to make it easier to read the workflow that will be created and tested. The results of this research are that the monitoring system with the Blynk Smartphone application turns on if the pH sensor gets a result of 7.2 causing it to open and the pH solution drops in the solenoid which will make nutrients flow into the water container. The solenoid will experience a closed condition because the sensor gets results in the range of 6.2 to 7.2 in pH units. The water level gets an average height of 18.5 to 19.5 cm with the sensor, nutrients are filled into the water container when the solenoid is triggered and turns off when it gets to the maximum value limit. Solar panels as an energy source for detecting acid bases in pH units and hydroponic nutrients are proven to be able to operate all devices within 24 hours during the period of growth.